Justicia social en la gestión de la administración pública ecuatoriana y derechos constitucionales - Diana Evelyn Hernández Gavilanes; Santiago Javier Páliz Ibarra; Elder Miguel Córdova Bósquez; Kléver Alfonso Pilamunga Yansapanta (Revista Ciencia Innovadora, 2026)
This article examines the relationship between the management of Ecuadorian public administration and the effective guarantee of constitutional rights linked to social justice, through a literature review combined with a field study conducted in public institutions located across the Ecuadorian highland’s region. A total of four hundred twenty users and three hundred eighty public servants were surveyed. Results show that sixty-four percent of users perceived equitable treatment, a figure that decreased among the indigenous population, where thirty-eight percent reported differentiated treatment. Seventy-eight percent of staff reported knowing the constitutional principles of equality and interculturality, although only forty-six percent had received recent formal training on these specific topics. Decentralized autonomous governments showed greater development of equity mechanisms, with fifty-eight percent compared to thirty-one percent among deconcentrated institutions, and institutions with more equity protocols reached institutional trust levels of four point zero out of five points. The study concludes that gaps persist between normative recognition and administrative practice, particularly regarding interculturality, communicational accessibility, and territorial equity, and recommends strengthening continuous staff training and disseminating rights-enforcement mechanisms among citizens across urban and rural territories alike.